Exosomes may be the carrier of acupuncture treatment for major depressive disorder - Lyu, Qin; Zhou, Xin; Shi, Liu-Qing; Chen, Hai-Yang; Lu, Mei; Ma, Xian-De; Ren, Lu (Frontiers in Behavioral Neuroscience, 2023)
The incidence of major depressive disorder (MDD) is increasing all over the world. There is a great need for complementary or alternative therapies with high safety, few side effects and precise efficacy to care of MDD. In China, acupuncture has rich laboratory data and clinical trials to demonstrate its antidepressant efficacy. However, there is no clear answer as to how it works. Exosomes are membranous vesicles that rely on cellular multivesicular bodies (MVBs) fused to the cell membrane for release into the extracellular matrix. Almost all cell types are capable of producing and releasing exosomes. As a result, exosomes contain complex RNAs and proteins from their relatives. They can cross biological barriers and participate in biological activities such as cell migration, angiogenesis, and immune regulation. These properties have made them a popular research topic. Some experts have suggested that exosomes may serve as delivery vehicles for acupuncture to work. This presents both an opportunity and a new challenge for improving the protocols of acupuncture for MDD. To better define the relationship between MDD, exosomes, and acupuncture, we reviewed the literature over the last few years. Inclusion criteria included randomized controlled trials and basic trials evaluating acupuncture in the treatment or prevention of MDD, the role of exosomes in the development and progression of MDD, and the role of exosomes in acupuncture. We believe that acupuncture may affect the distribution of exosomes in vivo, and exosomes may be a new carrier for acupuncture treatment of MDD in the future.